Eficiencia térmica de las calderas de vapor de la ciudad de Loja y su correlación con la contaminación ambiental. - Hidalgo Masache, Carlos Alberto (2016)
This present work was developed whit the purpose to determinate the correlation between the thermal efficiency of the steam boilers in City of Loja and the environmental pollution caused for the gas emissions generated by combustion. The development of the methodology was addressed from a descriptive-correlational perspective study; so that it was necessary the realization of data measurements in-situ of each boiler, which enabled the obtaining of different parameters, such as: pollutants agents that are expelled by chimney out to the atmosphere, technical characteristic, surface temperatures, surrounding and ambient. Starting from the obtained measurements, it was determined the thermal efficiency calculation (values between 63.88 % and 88.37 %). In addition, there were established the variables, which correlate, these are: sensible heat losses with flue exit gases and heat losses by incomplete combustion, it was proved with scatterplots and development of least squares. Correlation grade values between these variables determined that: the higher losses results from the gases emitted into the atmosphere, the more decrease of thermal efficiency. Also it evidenced that the analysis of correlation is independent for each boiler, due to their unique and specific conditions.